Design Principles of Nitrogen‐Doped Carbon Catalysts for Oxygen Reduction Reaction - Kenji Hayashida; Bang Lu; Satoru Takakusagi; Junji Nakamura; Kotaro Takeyasu (ChemElectroChem, 2025)
Nitrogen‐doped carbon catalysts are attracting significant attention as alternative electrocatalysts to platinum owing to their high activity and durability in fuel cells’ oxygen reduction reaction (ORR), resource availability, and low catalyst cost. Pyridinic nitrogen forms the active site of the ORR and that the reduction of pyridinium ions is discovered and adsorption of molecular oxygen are coupled with a unique reaction mechanism. The deactivation of nitrogen‐doped carbon catalysts in acid electrolytes is attributed to the protonation of pyridinic nitrogen and the associated hydration is reported. This concept is demonstrated by the increased activity of nitrogen‐doped graphene catalysts, whose hydrophobicity is enhanced by the 3D structure. To further enhance the catalytic activity of nitrogen‐doped carbon catalysts, the electronic configuration of the active sites, particularly the degree of electron localization and spin, plays a crucial role. As an example, the introduction of active sites through five‐membered ring structures is presented, along with their characterization by X‐ray absorption spectroscopy.